Improving The Ability of Posyandu Cadres and Breastfeeding Mothers In Oxytocin Stimulation And Breastfeeding SEFT “SOS Menyusui" As An Effort To Prevent Stunting - Tetet Kartilah; Sofia Februanti; Syaukia Adini (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Malnutrition is one of the biggest causes of morbidity and mortality in children under 5 years of age in developing countries related to metabolic, social, and environmental risk factors during the first 1000 days of life/HPK (from conception to the first 2 years of life). Stunting is the most common form of malnutrition in children, and exclusive breastfeeding for infants aged 0-6 months and continued until the child is 2 years old is an effort to prevent stunting. Breastfeeding mothers can experience various problems in the breastfeeding process, such as decreased production and smoothness of breast milk which can cause failure of exclusive breastfeeding. Breastfeeding training using Oxytocin Stimulation and SEFT breastfeeding (SOS Breastfeeding) for cadres and breastfeeding mothers with their families is an effort to maintain breast milk production and smoothness, through relaxation techniques and reducing stress levels to help minimize prolactin inhibitors and gentle massage for oxytocin stimulation to increase smoothness of breast milk. The training was attended by 7 cadres and 15 breastfeeding mothers with their families. The training method was conducted directly with lecture techniques, simulations, and demonstrations to Posyandu cadres, breastfeeding mothers, and their families. Participants were given a pretest, an explanation of the process of breast milk production and release, a simulation and demonstration of SOS breastfeeding, and a post-test. The results of the training showed an increase in the knowledge, attitude, and skills scores of cadres and breastfeeding mothers before and after training with an average knowledge and attitude score of 6.8 pretests (with the lowest score of 4 and the highest score of 8) and an average posttest score of 8.6 (the lowest score of 6 and the highest score of 10), and breastfeeding mothers and cadres were able to redemonstrate the SOS breastfeeding technique according to the guidelines. To maximize the results of the training, this activity requires ongoing cooperation between families with breastfeeding mothers, cadres, and regional midwives, to continue to improve the support system and interest in breastfeeding until the child is 2 years old.